2015
DOI: 10.1016/j.pmrj.2015.06.444
|View full text |Cite
|
Sign up to set email alerts
|

Walking Training and Functioning Among Elderly Persons With Stroke: Results of a Prospective Cohort Study

Abstract: Walking distance and both self-reported and measured functioning improved during walking rehabilitation among elderly persons who had a stroke. Maintaining or improving functioning through rehabilitation and self-administered exercises may be important in supporting mobility and independent living outside institutional care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
1
3
0
2
Order By: Relevance
“…In our study, the 6MWT revealed a considerable improvement in the patients’ physical status. Parallel results based on the same test were reported by Deskur-Śmielecka et al 21 Karttunen et al 22 reported that the walking distance and functioning improved during walking rehabilitation with the use of the 6MWT among elderly individuals after stroke. Perkowski et al 23 indicated a positive correlation between the 6MWT and upper and lower limb strength test scores.…”
Section: Discussionsupporting
confidence: 73%
“…In our study, the 6MWT revealed a considerable improvement in the patients’ physical status. Parallel results based on the same test were reported by Deskur-Śmielecka et al 21 Karttunen et al 22 reported that the walking distance and functioning improved during walking rehabilitation with the use of the 6MWT among elderly individuals after stroke. Perkowski et al 23 indicated a positive correlation between the 6MWT and upper and lower limb strength test scores.…”
Section: Discussionsupporting
confidence: 73%
“…La frecuencia dos veces por semana ha demostrado ser efectivo en el funcionamiento psicológico (Kekäläinen, Kokko, Sipilä, & Walker, 2017;Pires-Oliveira et al, 2014). Otra investigación obtuvo resultados beneficiosos en el dominio capacidad física del WHOQOL-BREF posterior a un entrenamiento de 6 meses en pacientes que sufrieron accidente cerebro vascular (Karttunen, Kallinen, Physician, Peurala, & Häkkinen, 2015).…”
Section: Discussionunclassified
“…Treadmills with several add-ons including virtual reality (omnidirectional treadmills) and robotic parts are often applied in elderly patients recovering from stroke as a walking rehabilitation program to improve physical function for affected body areas (e.g., shoulder and arms) and enhance as much as possible their neuroplasticity [ 19 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. In this respect, till today, several randomized clinical trials tried to evaluate the walking abilities using numerous approaches and exercises on treadmills, with also the application of obstacle crossing or other cognitive distractions, to evaluate their usability as adjuvant therapies in improving walking rehabilitation among people with stroke [ 18 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Thus far, the results from these trials suggest that for patients with stroke, retraining gait with the use of a treadmill and a percentage of their body weight supported (e.g., Lokomat ® robotic assistive device) or assisted through several wearables, resulted in improved postural abilities over those with no support on their body weight [ 18 , 24 , 36 , 41 , 44 , 71 , 73 , 74 , 75 , 76 ].…”
Section: Physiotherapy Interventions In the Elderly With Ndsmentioning
confidence: 99%